Does Corporate Ownership Structure Influence Firm Performance? Evidence from Indian corporate companies - Goud, N.Narsa (The Indonesian Journal of Accounting Research, 2024)
This research’s main aim is to examine the influence of ownership structure on financial and market performance using 260 Indian-listed companies on the BSE index as a sample size. The current study depends on the six-year economic dataset of the Bombay Stock Exchange (BSE) from FY 2014-15 to FY 2019-20. The firm’s performance is measured by two financial measures, ROE and ROA, and three marketing measures, namely EPS, Tobin’s Q, and Net Profit Margin (NPM). This study applied panel data models, such as pooled OLS, fixed effects, and random effects methods, along with the dynamic model of System-GMM intended for data analyses. This study found that the ownership concentration of the first single large (LSH1) significantly influences a firm’s performance with the ROE, EPS, and Tobin’s Q. However, ROA and NPM have a positive association with firms' performance. Similarly, the top five large (LSH5) ownership concentrations reported adverse influence on ROE, ROA, EPS, and NPM but indicated a positive association with Tobin’s Q performance measure. Regarding ownership identity, promotors, government, and domestic institutions have reported a negative influence on a firm’s performance but a positive influence on the market performance of Tobin’s Q and NPM. In addition, foreign institutions and individual ownership seemed to enhance financial and market performance. The current research’s significant contribution is the empirical investigation of two different characteristics of ownership concentration and identity, measured as ownership structure and firm performance.